The Philological-Pragmatic Approach : A Study of Language Choice and Code-Switching in Early Modern English School Performances - Mäkilähde, Aleksi (fi=Turun yliopisto|en=University of Turku|, 2019)
In this study I set out to account for certain central aspects of language choice and code-switching. My purpose is twofold: to explain why people use multiple languages within a single discourse or choose to use a particular language in a particular setting, and to demonstrate the feasibility and usefulness of combining philosophical and empirical research. Towards these ends, I develop a philological-pragmatic approach and apply it to a collection of multilingual texts. The material consists of the Orationes manuscript (Canterbury, Canterbury Cathedral Archives Lit. MS E41), containing speeches and plays in English, Latin, and Greek performed by students at the King’s School, Canterbury, in 1665–1684. I conduct a philosophical and methodological analysis of the philological-pragmatic approach, construct a framework on the basis of that analysis, and apply it in the empirical analyses to understand and explain actions. The philosophical and methodological analyses indicate that a basis for the philological-pragmatic approach can be constructed by reinterpreting philology and pragmatics from the perspective of action analysis and theory of action: philology as the study of concrete action-tokens (interpretation), pragmatics as the study of abstract action-types (explication and classification). The empirical analyses indicate that multilingual language use is an important and characteristic strategy in the Orationes texts. Three explanatory entities were central in accounting for multilingual language use: consequences of actions, causal antecedents, and further actions/forms. Consequences were classified into five basic categories: face-related, textual, argumentative, stylistic, and capacitative. These taxonomies sufficiently accounted for the patterns of language use observed in the dataset. The study constitutes the first book-length investigation of the Orationes texts. In addition to advancing our understanding of the roots of multilingual language use in the Early Modern English period, the patterns identified have several parallels both in different periods and in different cultures. Detecting such patterns has the potential to contribute to an integrated account of the phenomenon. Finally, the study offers other researchers a model for combining philology and pragmatics.

Käsittelen väitöskirjassani kielen valintaa ja koodinvaihtoa. Tutkimuksen tavoitteena on yhtäältä selittää, miksi yhden diskurssin sisällä käytetään useita kieliä tai tietyissä tilanteissa valitaan tietty kieli, ja toisaalta tuoda esiin hyötyjä, joita saadaan yhdistämällä filosofinen ja empiirinen tutkimus. Kehitän tutkimuksessani ns. filologis-pragmaattisen lähestymistavan ja sovellan sitä monikielisen tekstikokoelman analyysiin. Aineistoni koostuu Orationes-käsikirjoituksesta (Canterbury, Canterbury Cathedral Archives Lit. MS E41), joka sisältää Canterburyn King’s Schoolin oppilaiden vuosina 1665–1684 esittämiä puheita ja näytelmiä. Teksteissä käytettävät kielet ovat englanti, latina ja kreikka. Laadin filosofisen ja menetelmäopillisen kuvauksen filologis-pragmaattisesta lähestymistavasta, kehitän analyysin pohjalta viitekehyksen ja sovellan tätä viitekehystä tutkimuksen empiirisessä osassa tekojen ymmärtämiseen ja selittämiseen. Filosofisten ja menetelmäopillisten analyysien perusteella filologis-pragmaattinen lähestymistapa voidaan rakentaa määrittelemällä filologia ja pragmatiikka tekojen tutkimisen näkökulmasta: filologia tutkii konkreettisia tekoesiintymiä (menetelmänä tulkinta), pragmatiikka abstrakteja tekotyyppejä (menetelminä eksplikaatio ja luokittelu). Empiirisen analyysin perusteella monikielinen kielenkäyttö on keskeinen osa Orationes-tekstejä. Selityksissä viittasin erityisesti tekojen seurauksiin, kausaalisiin tekijöihin sekä muihin tekoihin/rakenteisiin. Luokittelin tekojen seuraukset edelleen kasvoihin liittyviin, tekstuaalisiin, argumentatiivisiin, stilistisiin ja mahdollistaviin. Näiden taksonomioiden avulla pystyin selittämään tutkittavat ilmiöt aineistossani. Väitöstutkimukseni on ensimmäinen laaja tutkimus Orationes-teksteistä. Tutkimuksen tulokset auttavat ymmärtämään monikielisen kielenkäytön juuria 1600-luvun Britanniassa. Vertaamalla tuloksia aiempiin tutkimuksiin löydetään yhtymäkohtia eri aikakausilta ja eri kulttuureista. Näitä yhtymäkohtia tarkastelemalla saavutetaan entistä kattavampi käsitys monikielisen kielenkäytön luonteesta. Tutkimukseni tarjoaa myös yleisen mallin filologian ja pragmatiikan yhdistämiseen.